IMPACT OF SNAKE BITES AND DETERMINANTS OF FATAL OUTCOMES IN SOUTHEASTERN NEPAL - Sanjeev Sharma; François Chappuis; Nilhambar Jha; Patrick Bovier; Louis Loutan; Shekhar Koirala (2004)
Current available data on snake bites in Nepal are based solely on hospital statistics. This community-based study aimed at evaluating the impact of snake bites and determining the risk factors associated with a fatal outcome in southeastern Nepal. A total of 1,817 households, selected by a random proportionate sampling method, were visited by trained fieldworkers in five villages. Extensive data from snake bite victims during the 14 previous months were recorded and analyzed. One hundred forty-three snake bites including 75 bites with signs of envenoming were reported (annual incidence = 1,162/100,000 and 604/100,000, respectively), resulting in 20 deaths (annual mortality rate = 162/100,000). Characteristics of krait bites such as bites occurring inside the house, while resting, and between midnight and 6:00 am were all factors associated with an increased risk of death, as were an initial consultation with a traditional healer, a long delay before transport, and a lack of available transport. An initial transfer to a specialized treatment center and transport by motorcycle were strong protective factors. Among the 123 survivors, wounds required dressing and surgery in 30 (24%) and 10 (8%) victims, respectively, the mean working incapacity period was 15 days, and the mean out-of-pocket expense was 69 U.S. dollars. Snake bite is a major but neglected public health problem in southeastern Nepal. Public health interventions should focus on improving victims’ rapid access to anti-snake venom serum by promoting immediate and fast transport to adequate treatment centers, particularly for bites occurring at night.